Assessment of a circular powered stapler for creation of anastomosis in left-sided colorectal surgery: A prospective cohort study. (December 2020) - Herzig, Daniel O.; Ogilvie, James W.; Chudzinski, Allen; Ferrara, Andrea; Ashraf, Shazad Q.; Jimenez-Rodriguez, Rosa M.; Van der Speeten, Kurt; Kinross, James; Schimmelpenning, Hendrik; Sagar, Peter M.; Cannon, Jamie A.; Schwiers, Michael L.; et al.
Abstract: Background: Circular staplers perform a critical function for creation of anastomoses in colorectal surgeries. Powered stapling systems allow for reduced force required by surgeons to fire the device and may provide advantages for creating a secure anastomosis. The objective of this study was to evaluate the clinical performance of a novel circular powered stapler in a post-market setting, during left-sided colectomy procedures. Materials and methods: Consecutive subjects underwent left-sided colorectal resections that included anastomosis performed with the ECHELON CIRCULAR™ Powered Stapler (ECP). The primary endpoint was the frequency in which a stapler performance issue was observed. Secondary endpoints included evaluation of ease of use of the device via a surgeon satisfaction questionnaire, and monitoring/recording of procedure-related adverse events (AEs). Results: A total of 168 anastomoses were performed with the ECP. Surgical approaches included robotic-assisted (n = 74, 44.0%), laparoscopic (n = 71, 42.3%), open (n = 20, 11.9%), and hand-assisted minimally invasive (n = 3, 1.8%) procedures. There were 22 occurrences of device performance issues in 20 (11.9%) subjects during surgery. No positive intraoperative leak tests were observed, and only 1 issue was related to a procedure-related AE or surgical complication, which was an instance of incomplete surgical donut necessitating re-anastomosis. Postoperative anastomotic leaks were experienced in 4 (2.4%) subjects. Clavien-Dindo classification of all AEs indicated that 92.0% were Grades I or II. Participating surgeons rated the ECP as easier to use compared to previously used manual circular staplers in 85.7% of procedures. Conclusion: The circular powered stapler exhibited few clinically relevant performance issues, an overall favorable safety profile, and ease of use for creation of left-sided colon anastomoses. Highlights: Test device performance issues occurred in 20 (11.9%) subjects with only one issue requiring surgical revision. There were zero (0%) intraoperative leaks and 4 (2.4%) postoperative anastomotic leaks among 168 procedures. The circular powered stapler demonstrated ease of use as judged by investigators.